New silhouette detection algorithm to create real-time volume shadow - Kolivand, H. (IEEE, 2011)
In this paper a new algorithm to recognize occluder silhouette for generating shadow volume with some improvement of the traditional shadow volume algorithm is proposed. Silhouette detection is one of the expensive processes of volume shadows (VS). The triangular algorithm and visible-non-visible algorithm that are famous algorithms to detect the outline of occluder are renewed. An accurate comparison between these algorithms and a new algorithm has been done. The algorithm involves to detect silhouette and decreases the cost of implementation of VS. The obtained results confirm superiority of the proposed algorithm in terms of processing time to the previously used traditional algorithms. The last volume shadow algorithm using stencil buffer is rewritten and an algorithm for VS with silhouette detection together is proposed. It makes higher the number of frame per second.